2002
DOI: 10.1207/s15374424jccp3104_7
|View full text |Cite
|
Sign up to set email alerts
|

An Affect-Based, Hierarchical Model of Temperament and Its Relations With Internalizing Symptomatology

Abstract: Examined the tripartite model of personality, which emphasizes negative affectivity (NA) and positive affectivity (PA) as central organizing dimensions of personality that are useful for discriminating psychopathologies. Conceptualizations of youth temperament also include second-order, organizing factors of negative emotionality/neuroticism and positive emotionality/extroversion that may differentially predict psychopathologies. A community sample of 290 10- to 17-year-old youth completed the Emotionality, Ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
50
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(56 citation statements)
references
References 40 publications
6
50
0
Order By: Relevance
“…More recently attention has shifted to models which examine the interplay between these temperamental factors, with emerging evidence supporting the combination of high levels of negative affect and low levels of effortful control in the prediction of childhood internalizing symptoms. Specifically, research supports the combined role of high trait emotional reactivity with low levels of self-regulatory abilities to modulate these reactions as a primary risk factor for developing internalizing symptoms in childhood [7][8][9].…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…More recently attention has shifted to models which examine the interplay between these temperamental factors, with emerging evidence supporting the combination of high levels of negative affect and low levels of effortful control in the prediction of childhood internalizing symptoms. Specifically, research supports the combined role of high trait emotional reactivity with low levels of self-regulatory abilities to modulate these reactions as a primary risk factor for developing internalizing symptoms in childhood [7][8][9].…”
Section: Introductionmentioning
confidence: 92%
“…Research has shown that children with specific patterns of high emotional reactivity and decreased attention regulation are more prone to experiencing symptoms of internalizing disorders [7][8][9]. In addition, maternal traits such as negative emotional reactivity and neuroticism have been associated with more controlling and hostile parenting and interaction styles [10,11], which have also been associated with child internalizing disorders.…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, the age distribution was as follows: 18.9, 19.7, 16.8, 16, 11.3, 11.8 and 5.5% for age 8,9,10,11,12,13, and 14 respectively. From this total sample, 75.7% (n = 184) participated in wave 2 and 24.3% (n = 59) did not participate in wave 2.…”
Section: Referred Samplementioning
confidence: 98%
“…In the study of Chorpita et al (2000b), for instance, the paths from NA to depressive disorder, social anxiety and separation anxiety did not reach significance. In contrast, other researchers do find support in children or adolescents for the divergent relation of PA or PH and the generality assumption as predicted by the tripartite model (Anthony et al 2002;Crook et al 1998;Laurent et al 2004Laurent et al , 1999Lonigan et al 2003;Phillips et al 2002).…”
mentioning
confidence: 93%